More creative through positive mood? Not everyone! - Akbari Chermahini, Soghra; Hommel, Bernhard (Frontiers in Human Neuroscience, 2012)
It is commonly assumed that positive mood improves human creativity and that the neurotransmitter dopamine might mediate this association. However, given the non-linear relation between dopamine and flexibility in divergent thinking (Akbari Chermahini & Hommel, 2010), the impact of mood on divergent kinds of creativity might depend on a given individual’s tonic dopamine level. We tested this possibility in adults by assessing mood, performance in a divergent-thinking task (the Alternate Uses Task), and eye-blink rates (EBRs), a well-established clinical marker of the individual dopamine level, before and after positive-mood or negative-mood induction. As expected, the association between flexibility in divergent-thinking performance and EBR followed an inverted U-shape function (with best performance for medium levels), positive mood induction raised EBRs and only individuals with below-median EBRs, but not those with above-median EBRs, benefited from positive mood. These observations provide support for dopamine-based approaches to the impact of mood on creativity and challenge the generality of the widely held view that positive mood facilitates creativity.